Effects Of A Combination Of Microscopic Handgrip And Nature's Voice On A Client's Blood Pressure With Hypertension - Margiyati Margiyati; Novita Wulansari (International Journal of Medicine and Health, 2024)
Background: Hypertension is the number one cause of death in the world every year because it causes complex cardiovascular problems. Semarang City Department's 2023 health profile data shows the number of hypertension is 24,949. Practicing holding a handgrip is a non-pharmacological therapy for treating hypertension because it stabilizes blood pressure and heart rate. Many combination therapies are used, including combining handgrip exercises with sound waves. Natural sounds will stimulate the hypothalamus, resulting in a feeling of calm and have an effect on the blood pressure regulation mechanism. The aim of this study was to determine the effect of a combination of handgrip exercise and natural sounds on the blood pressure of clients with hypertension. This research method is a pre-experimental one group pre and post test design and sampling using purposive sampling technique. The population of this study were clients who were recorded as suffering from hypertension at the Sekaran Semarang Community Health Center. The research instrument uses a digital spygmomanometer and SOP for action. The research stages consist of preparation, implementation and processing of research data. The steps in the preparation stage are literature study, field survey, discussions with lecturers and experts, developing procedures for the combination of handgrip exercise and natural sounds, expert review, and socialization of the combination of handgrip exercise and natural sounds to clients and families. The implementation stage is carried out by collecting data on clients registered at the Sekaran Semarang Community Health Center, pre and post tests by measuring blood pressure using a spygmomanometer, implementing actions according to the prepared SOP, observing implementation using an observation sheet. In the data processing stage, a Paired Sample T-test was carried out to assess the effect of the combination of handgrip exercise and natural sounds on the blood pressure of clients with hypertension. The targeted output is publication in national journals indexed by Sinta and HAKI. The TKT target for this combination of handgrip exercise and natural sounds is level 2. The research results showed that 91.67% of respondents experienced an average reduction in systolic blood pressure of 10.69 mmHg and diastolic blood pressure of 6.11 mmHg. Based on the Paired Sample T-test, the results obtained were 0.000 for the systolic value and 0.001 for the diastolic value, both of which were smaller than the p value of 0.05, so it was concluded that there was an influence of the combination of handgrip exercise and natural sounds on the blood pressure of clients with hypertension. The results of this research can be input for related parties to implement a combination of handgrip exercise and natural sounds as non-pharmacological therapy for hypertension sufferers.